Experience-Specific Dimensions of Consciousness (Observable in Flexible and Spontaneous Action Planning Among Animals) - Kaufmann, Angelica (Frontiers in Systems Neuroscience, 2021)
The multidimensional framework to the study of consciousness, which comes as an alternative to a single sliding scale model, offers a set of experimental paradigms for investigating dimensions of animal consciousness, beautifully acknowledging the urge for a novel approach. One of these dimensions investigates whether nonhuman animals can flexibly and spontaneously plan for a future event, and for future desires, without relying on reinforcement learning. This is a critical question since different intentional structures for action in non-human animals are described as served by different neural mechanisms underpinning the capacity to represent temporal properties. And a lack of appreciation of this variety of intentional structures and neural correlates has led many experts to doubt that animals have access to temporal reasoning and to not recognize temporality as a mark of consciousness, and as a psychological resource for their life. With respect to this, there is a significant body of ethological evidence for planning abilities in nonhuman animals, too often overlooked, and that instead should be taken into serious account. This could contribute to assigning consciousness profiles, across and within species, that should be tailored according to an implemented and expansive use of the multidimensional framework. This cannot be fully operational in the absence of an additional tag to its dimensions of variations: the experience-specificity of consciousness.